Optimal Earnings-Related Unemployment Benefits - Mohammad Taslimi (Uppsala University, Department of Economics, 2003)
Existing unemployment insurance systems in many OECD countries involve a ceiling on insurable earnings. The result is lower replacement rate for employees with relatively high earnings. This paper examines whether replacement rates should decrease as the level of earnings rises. The framework is a search equilibrium model where wages are determined by Nash bargaining between firms and workers, job search intensity is endogenous and workers are heterogeneous. The analysis suggests higher replacement rates for low-paid workers if taxes are uniform. The same result may hold when taxes are redistributive. Numerical simulations indicate that there are modest welfare gains associated with moving from an optimal uniform benefit system to an optimally differentiated one in both cases, i.e., uniform and redistributive taxation. The case for differentiation arises from the fact that it may have favourable effects on the tax base.
urn:nbn:se:uu:diva-4484
Keywords: D81; D83; J64; J65; 330; Unemployment insurance; Unemployment; Search; Arbeitslosenversicherung; Arbeitslosigkeit; Arbeitsuche; OECD-Staaten